The use of an embryo transfer simulator to compare transfer techniques and pregnancy outcomes among physicians - Dana B. McQueen, M.D; Ali Borazjani, M.D., Ph.D; Chen Yeh, M.S; Siyuan Dong, M.S; Magdy P. Milad, M.D., M.S; Eve C. Feinberg, M.D (Elsevier, 2024)
Objective: To evaluate the association between embryo transfer techniques and pregnancy outcomes. Design: This is a prospective observational study with a retrospective cohort. Setting: University Clinic. Patients: Patients underwent embryo transfers between 2015 and 2020. Intervention/Exposure: Fourteen physicians performed 25 mock embryo transfers on the embryo transfer simulator and completed a questionnaire assessing preferred embryo transfer techniques. Quantitative performance metrics on the embryo transfer simulator were measured. Individual physician embryo transfer success rates were retrospectively collected from all fresh and cryopreserved embryo transfers between January 1, 2015, and January 1, 2020. Associations between embryo transfer techniques (preferred technique and simulator performance metrics) and each physician's historical patient pregnancy outcomes were assessed. Main Outcome Measures: Associations between embryo transfer techniques and live births were assessed. Results: There were significant differences in embryo transfer techniques between physicians, including touches to the fundus, distance to the fundus, duration of embryo transfer, duration of the complete procedure, time spent navigating the cervical canal, velocity of embryo expulsion, time waited after embryo expulsion, and total score on the embryo transfer simulator. After controlling for confounders and multiple transfers per physician, the duration of embryo transfer was significantly associated with live birth, with longer durations associated with decreased live birth rates. Shorter placement distance to the fundus and higher velocity of embryo expulsion were both significantly associated with higher rates of ectopic pregnancy. Conclusions: This study revealed significant differences in transfer techniques among physicians. The use of the embryo transfer simulator for physicians in practice can elucidate differences and create opportunities for data-driven improvement in embryo transfer success rates.